2021
DOI: 10.3390/nu13082547
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of a Newly Developed Technology-Mediated Lifestyle Intervention for Overweight and Obese Young Adults

Abstract: Background: Poor eating habits and sedentary lifestyle are common among young adults and increase the risk for chronic diseases later in life. Due to the widespread use of information technology among young adults, the Rashakaty (Fitness for Me) study aimed to develop and test the feasibility of a technology-based nutrition education intervention. This would support overweight and obese university students to achieve weight loss, enhance nutrition knowledge, and increase physical activity levels. Methods: We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 42 publications
0
48
0
Order By: Relevance
“…In order to identify independent effects of CPD on mental health for college students, other related characteristics must be controlled. We take into account age (Xie et al, 2019b ), grade (Dou et al, 2020 ), gender (Lu et al, 2018 ), monthly allowance (Li et al, 2020 ), Faculty-Student relationship (Liang and Liu, 2021 ), substance use (Carreiro et al, 2018 ), physical exercise (Zhong and Wang, 2020 ), insomnia (Zhang et al, 2021 ), obesity (Ali et al, 2021 ), life satisfaction (Kuang-Tsan, 2017 ), and subjective wellbeing (SWB) (Ye et al, 2021 ) to confirm the salient effect of CPD and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify independent effects of CPD on mental health for college students, other related characteristics must be controlled. We take into account age (Xie et al, 2019b ), grade (Dou et al, 2020 ), gender (Lu et al, 2018 ), monthly allowance (Li et al, 2020 ), Faculty-Student relationship (Liang and Liu, 2021 ), substance use (Carreiro et al, 2018 ), physical exercise (Zhong and Wang, 2020 ), insomnia (Zhang et al, 2021 ), obesity (Ali et al, 2021 ), life satisfaction (Kuang-Tsan, 2017 ), and subjective wellbeing (SWB) (Ye et al, 2021 ) to confirm the salient effect of CPD and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by Bonofiglio [42], stating that when a high level of physical activity is carried out, there is a tendency to improve the diet, this being due to the practice of sport at a competitive level. In contrast, very distant results were found by Malakou et al [43], with Ali et al [44] stating the need for more training in the educational environment.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies reported sociocultural barriers to a healthy lifestyle among the Arab population, particularly among women [21][22][23][24][25]. Lifestyle intervention programs should be adapted to cultural and religious practices to be effective [26]. Hence, there is a need for community-based and culturally acceptable interventions in Arab countries [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle intervention programs should be adapted to cultural and religious practices to be effective [26]. Hence, there is a need for community-based and culturally acceptable interventions in Arab countries [26][27][28]. To date, only a few review-based studies have been conducted in Arab countries, focusing on interventional programs, limited to physical activity only [25,29,30] or interventions led by specific healthcare providers such as pharmacists [31], and targeting different NCDs.…”
Section: Introductionmentioning
confidence: 99%